Alle radici del senso di Sé Proposte per uno studio sull’emergere della consapevolezza corporea nella prima infanzia - Alfonso Davide Di Sarno, Vania Costa, Rita Di Gennaro, Giuseppina Di Leva, Irene Fabbricino, Daniela Iennaco, Teresa Longobardi, Martina Messina, Enrico Moretto, Lucia Luciana Mosca (Phenomena Journal)
To define the Self is extremely complex, because the same nature of the object that we propose ourselves to study, if it is relatively difficult to say what is not, the task to explain it becomes extremely arduous if we try to define what it is. The more developed and known field of the neuroscience is in fact the one that studies the phenomenon of the conscience and the sense of himself on the pathological depositor, when as a result of cerebral lesions, degenerative diseases and/or incidents events some part of the brain, as a result of the damage, become inactive, creating a structural change of the cerebral functions, the emotional management and the identity. The study of the conscience and emerging of Self has always implied a “reduction”: the identity, is reduced to an artifact semantic linguistic/or a function of self monitoring. In this article some of the most credited theories about the emerging of the self awareness in early childhood and its neurobiological basis are brought back, in order to succeed to define in which way these theories have influenced the way we conceive the psycopathogenesis and the modalities of treatment tied to psychic disorders.